Definition of learning approaches of future process engineers of food industry - Lazareva, T.; Rybakova, O. (Problems of Engineer-Pedagogical Education, 2018)
In the article claims-centered, active, systematic and qualified approach to training future engineers the food industry. Determined that the study should be directed to the formation of identity, self-development and self-realization of future professionals develop their intelligence, thought, imagination, memory and ability to hold receptions mental activity. The content of education should be developed specific to the food industry, with emphasis on the formation of action on stereotypical professional activities, diagnostic and heuristic levels. As is training future engineers the food industry is a system formed of subsystems presentation and learning and their own food production technologies are the system because the training of future engineers the food industry is important to consider the principles of the system approach. Also, the article analyzes and formed a purpose of training future professionals of the food industry, and identified requirements for professional-important qualities of future specialists.